Toolkit in statistics on android mobile devices. - Rio, Kent (UPHSI, 2015)
The main goal of this study is to create an acceptable statistical toolkit application for mobile android devices. This application was created to help students having a hard time solving statistical problems. It is a means to simplify the solving process of the usher whether it is for schoolwork or research purposes. The application was named PocketStat and it will be released to the public via Google Play Store and will be free of charge. It was developed in the programming language Java and runs only on the OS Android. This study will determine the acceptability and the accuracy of the application. Results showed that the interface and appearance features of the PocketStat were acceptable to the respondents. On the other hand, the accuracy and usefulness features of the application were found by the respondents to be highly acceptable.